(untitled) (Clinics, 2013)
OBJECTIVE: Leukocyte-associated immunoglobulin-like receptor-1 is an inhibitory receptor primarily expressed by immune cells. This study was undertaken to define the role of this molecule in osteoclast differentiation and rheumatoid arthritis. METHODS: In vitro osteoclast assays were performed to characterize the role of Leukocyte-associated immunoglobulin-like receptor-1 in murine and human osteoclastogenesis. Human Leukocyte-associated immunoglobulin-like receptor-1 expression was assessed by immunohistochemistry staining in the synovium of patients with rheumatoid arthritis. The levels of soluble Human Leukocyte-associated immunoglobulin-like receptor-1 were determined by enzyme-linked immunosorbent assay. RESULTS: We found that multinucleated osteoclast formation from mouse bone marrow cells was inhibited by treatment with a monoclonal antibody against mouse Leukocyte-associated immunoglobulin-like receptor-1 in vitro. By immunohistochemistry, we found that Leukocyte-associated immunoglobulin-like receptor-1 was mainly expressed by macrophages in the inflamed synovial tissue of rheumatoid arthritis patients. In addition, serum and synovial fluid levels of soluble Leukocyte-associated immunoglobulin-like receptor-1 were higher in rheumatoid arthritis patients compared to healthy controls or osteoarthritis patients. Moreover, overexpression of Leukocyte-associated immunoglobulin-like receptor-1 in CD14+ monocytes from healthy volunteers also inhibited human osteoclastogenesis. CONCLUSION: Collectively, these data demonstrate for the first time that Leukocyte-associated immunoglobulin-like receptor-1 inhibits osteoclastogenesis. Therefore, these results may have therapeutic implications for the treatment of rheumatoid arthritis.